2018
DOI: 10.1007/s00586-018-5729-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of muscle ageing and sarcopenia on spinal segmental loads

Abstract: The study highlights the distinct and detrimental consequences of sarcopenia, in contrast to normal ageing, on spinal loading and required muscular effort. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Women generally have lower muscle mass than men with a higher prevalence of vertebral fragility fractures, which could be a result of the loss of protective muscle mass [19]. Ignasiak et al [20] simulated the effect of aging and sarcopenia in a spine model to determine muscle recruitment patterns and spinal loads. They simulated the loss of muscle fibers of back extensors, erector spinae, and multifidus that occurs with normal aging and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Women generally have lower muscle mass than men with a higher prevalence of vertebral fragility fractures, which could be a result of the loss of protective muscle mass [19]. Ignasiak et al [20] simulated the effect of aging and sarcopenia in a spine model to determine muscle recruitment patterns and spinal loads. They simulated the loss of muscle fibers of back extensors, erector spinae, and multifidus that occurs with normal aging and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Based on aging from the third to the sixth decade of life, ≥60% of normal strength, sarcopenia is mild of 60% strength, moderate of �8% strength, severe of 36% strength, very severe of 2�% strength. These results revealed that severe and very severe stages of sarcopenia were associated with substantial increases up to 318 N of compression at the levels of the upper thoracic spine, and up to 176 N of shear loading along the thoracolumbar spine [22]. Schlaeger et al [23] reported that proton density fat fraction (PDFF) of MRI in erector spinae muscle could be related to muscle strength.…”
Section: Discussionmentioning
confidence: 95%
“…Briggs et al [21] mentioned that intervertebral disc integrity as well as paravertebral muscle strength would prevent the spine from suffering vertebral fracture. Moreover, Igna-siak et al [22] reported that several stages of aging and sarcopenia were modeled by identifying reduced strength of erector spinae and multifidus muscles. Based on aging from the third to the sixth decade of life, ≥60% of normal strength, sarcopenia is mild of 60% strength, moderate of �8% strength, severe of 36% strength, very severe of 2�% strength.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies investigated the whole spine to determine the association between kyphosis and spinal loads in vertebral bodies and intervertebral discs [10] ing the radiographic data from patients with kyphosis, and concluded that increases in thoracic kyphosis were associated with significantly higher multi-segmental spinal load and trunk muscle forces in the upright stance [12]. Ignasiak et al investigated the effects of muscle aging and sarcopenia on spinal load using generic AnyBody musculoskeletal multibody modeling, which was similar to our original model [24]. In their study which highlighted the effect of muscle or sarcopenia, forward flexion of the whole spine was simulated to observe changes in spinal load.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several biomechanical studies using a musculoskeletal model of the entire spine, including the rib cage or whole body, have been developed [10] [21] [22] [23] [24]. We also developed a novel musculoskeletal model of the entire spinal column, which was modified from the original model for the lumbar spine, which included the thoracic cage as one rigid body [23].…”
Section: Introductionmentioning
confidence: 99%